Flow optimization strategies - Gallien, Jérémie (Henry Stewart Talks, 2012)
Definition and motivation, Optimization methodology overview, Industrial case study 1: Inbound routing optimization at Dell, Industrial case study 2: Distribution optimization at Zara, Conclusion and follow-up references